Jual-Beli Narkotika Dikaitkan Dengan Hukum Islam - Akbar Sanjaya (Yayasan Studi Cendekia Indonesia (YSCI), 2023)
Narcotics are substances or drugs that can cause changes in consciousness, loss of pain, and addiction. The potential dangers of narcotics have led to the enactment of Law No. 35 of 2009 concerning Narcotics. Narcotics come in various forms such as pills, powders, plants, and liquids, although not all narcotics are in liquid form. This study aims to analyze the view of Islamic Criminal Law regarding the trade of narcotics. The study uses a normative legal research method by using secondary data, namely legislation, books, journals, and other secondary data related to the object of research and analyzed qualitatively. The results show that the sale and purchase of goods, or ma’kud ‘alaih (object), require that the object of the sale and purchase must be pure and beneficial, which means that the object of the sale and purchase must be lawful and beneficial for the body and soul of the buyer. Narcotics are substances that can eliminate consciousness and reason of a person, and are included in the category of Khamr that is prohibited in Islam.